Three‐dimensional conformal radiation therapy for inoperable massive hepatocellular carcinoma in six dogs. (28th March 2015) - Mori, T.; Ito, Y.; Kawabe, M.; Iwasaki, R.; Sakai, H.; Murakami, M.; Maruo, K.
<x xml:space="preserve">Abstract</x> OBJECTIVES To evaluate the activity and tolerability of three‐dimensional conformal radiation therapy (3D‐CRT) in dogs with massive hepatocellular carcinoma. MATERIALS AND METHODS Six dogs with massive hepatocellular carcinoma that were ineligible for surgical resection or with owners who declined surgical resection, and underwent 3D‐CRT were retrospectively reviewed. 6 to 10 Gy per fraction was prescribed at isocentre of planning target volume to a total dose of 18 to 42 Gy with 1 to 2 fractions per week for a total of 3 to 7 fractions. Follow‐up examinations included physical examination, contrast‐enhanced CT scan and blood analysis (complete blood count, electrolytes and serum biochemical panel). RESULTS The median follow‐up time after 3D‐CRT was 534 (range, 281 to 1057) days. An objective response was observed in five of six cases. Radiation‐induced liver disease developed in one dog but was asymptomatic and reversible. Toxicity was not noted in any other dog. CLINICAL SIGNIFICANCE 3D‐CRT appears to be a viable treatment option for dogs with inoperable massive hepatocellular carcinoma.